Dostupné bydlení, Berlín - Chervonnyy, Roman; Roman Chervonnyy (České vysoké učení technické v Praze, 2022)
Zadáním této bakalářské práce byl návrh sociálního bydleni a případně dalších funkci. Cílem moje práci bylo co nejvíc řešit problémy, které jsou charakteristické pro toto území, a taky zlepšit kvalitu života jak v objektu, tak i v okolí.

The assignment of this bachelor's thesis was the proposal of social housing and possibly other functions. The aim of my work was to solve as much as possible the problems that are characteristic of this area, and also to improve the quality of life both in the building and in the surroundings.
Affordable Housing
Keywords: Berlín; zelená fasáda; bytový dům; mríž; bříza; Berlin; green facade; apartmens building